CO2 Capture from Dilute Sources via Lime-Based Sorbents - Samari, Mohammad (Université d'Ottawa / University of Ottawa, 2014)
Direct capture of CO2 from ambient air is a developing technology, which is capable of removing CO2 directly from the atmosphere. Moreover, this technology is independent from sources of CO2 emissions. Hence, it can be set up at locations where pure stream of CO2 is needed such as in enhanced oil recovery. In this research, the performance of pelletized and natural limestone for CO2 capture from air in a fixed bed is studied. To compare the performance of sorbents for air capture, the effects of particle type (natural limestone and pelletized limestone), particle size (250-425 µm and 425-600 µm), gas flowrate (0.5 L/min and 1 L/min), and relative humidity, on the breakthrough time, breakthrough shape, and the global reaction rate are examined. Moreover, carbonation decay of sorbents over series of capture and regeneration cycles is studied. If the inlet stream (air) is humidified at 50% relative humidity, but the lime sorbents are not pre-hydrated, an axially non-uniform carbonated bed results. This phenomenon is due to the partial carbonation of sorbents at the first layers of the bed. While there is a competition between CO2 and water to react with CaO, partial carbonation reaction on the surface of the sorbents not only prevents further hydration, but also decreases the reaction rate at the surface. However, in comparison with a dry system where relative humidity was negligible and sorbents were not pre-hydrated, the observed carbonation conversion was higher. The best results were seen from experiments with pre-hydrated sorbents and humidified inlet stream. The smaller sorbent particles had a better performance (sharper breakthrough curve and longer breakthrough time) due to their greater surface area. A gas-solid reaction model was fitted to the breakthrough curves. Since at the beginning of carbonation there is no resistance of the product layer, it can be assumed that the process is reaction controlled. While after formation of the product layer (CaCO3), it becomes diffusion controlled. Results from fitted data also confirmed these conclusions. Moreover, each of sorbent went through 9 cycles and after each cycle the carbonation conversion of the sorbents was measured by TGA and the surface area by BET.
Keywords: Direct Air Capture; Lime-Based Sorbents